PENGUKURAN BEBAN KERJA PEKERJA DI UD. BINTANG JAYA MANDIRI MENGUNAKAN CVL DAN NASA-TLX - Puyuhiyo, Zulqarnain; Wolok, Eduart; Lahay, Idham Halid (RADIAL : Jurnal Peradaban Sains, Rekayasa dan Teknologi, 2024)
Abstract: Measuring Workload of Workers at UD. Bintang Jaya Mandiri uses CVL and NASA-TLX The amount of physical and mental load depends on the level of difficulty of each activity, causing different workloads. The method for measuring physical workload uses the %CVL (Cardiovascular Load) method, while the method for measuring mental load uses the NASA-TLX (National Aeronautics and Space Administration Task Load Index) method. Calculation results from workers at UD. Bintang Kaya Mandiri used the %CVL method in shift I. The values ​​obtained were classified as "Medium" (30% to ≤ 60%) "Required improvement but not urgent" for 18 people and classified as "Low" (≤ 30%) "There is no fatigue in workers" as many as 2 people, while shift II scores obtained were classified as "Medium" (30% to ≤ 60%) "Required improvement but not urgent" as many as 16 people and classified as "Low" (≤ 30%) "There is no fatigue among workers ” as many as 4 people. Measuring mental load using the NASA-TLX method in shift I, the scores obtained were classified as "Quite High" (30-49) by 1 person and classified as "High" (50-79) by 19 people, while in shift II the scores obtained were classified as " Fairly High” (30-49) as many as 3 people and classified as “High” (50-79) as many as 17 people.